Enhancing Critical Thinking, Communication Skills, and Self Confidence through Inquiry Based Learning in Secretaryship Courses - Budiman, Muhammad Arief; Wahyuni, Sri; Wisnu, Mohamad Faqih; Rahman, Muhammad Adiyatur; Kholid, Muhammad Kharrisma Idhom; Abror, Muhammad Zidnal (Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates the effects of inquiry-based learning (IBL) on critical thinking dispositions, communication skills, and self-confidence of vocational English as a Foreign Language (EFL) students in a Secretaryship course at a Faculty of Language Education in Indonesia. A mixed-methods design was employed with 15 students, combining quantitative assessment using the Communication, Teamwork, and Self-Confidence Questionnaire (CTSQ) and qualitative data from students’ reflective journals. The CTSQ measured six dimensions: truth-seeking, open-mindedness, analyticity, systematicity, critical thinking self-confidence, and inquisitiveness. Descriptive statistics showed improvements in all dimensions, with the overall mean increasing from 4.63 to 4.88, indicating a positive impact of IBL on students’ cognitive and affective dispositions. Qualitative analysis revealed three main themes: development of practical professional skills, enhancement of conceptual understanding, and strengthening of soft skills, including communication, collaboration, and self-confidence. Students reported that role-play, scenario-based tasks, and inquiry-oriented activities increased their engagement, allowed them to practice real-world professional interactions, and fostered autonomous learning. Overall, the findings suggest that IBL is an effective pedagogical approach for integrating critical thinking, communication competence, and confidence in vocational EFL education. The study contributes evidence-based guidance for designing learner-centered instruction that bridges theory and professional practice.